Spawning, Larval Rearing and Early Growth of Siganus Guttatus (Bloch) (Pisces: Siganidae) - Alcazar, Sally; Luchavez, Julieta (Silliman Journal, 2024)
The. successful spawning and larval rearing of Siganus guttatus (Bloch) up to the post-metamorphosis stage is reported. §. guttatus generally spawns within the first quarter moon, laying an estimated half million eggs. The incubation period lasts for about 24 hours. Newly hatched larvae depend on yolk and oil globules for nourishment. They begin feeding on day two, when the yolk and oil globules have been almost consumed. Complete metamorphosis is observed to occur on day 30. Larval survival depends on (1) adequate and proper food and (2) sub-toxic nitrite concentration in the rearing container.